Pengaruh Lembar Kerja Peserta Didik Berbasis Collaborative Teamwork Learning Terhadap Hasil Belajar: The Effect of Collaborative Teamwork Learning Based Students on Learning Outcomes - Sholeha, Dwi Siti; Suyatna, Agus; Herlina, Kartini (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to determine the effect of using student worksheets based on collaborative teamwork learning on student learning achievement. The research design used was One Shot Case Study and One Group Pretest Posttest Design. The research data was taken from the value of observations and initial and final tests whose results were tested using the One Sample T-Test and Paired Sample T-Test. Based on the results of hypothesis testing using one sample t-test with Asymp.Sig. (2-tailed) values obtained ≤ 0.05 so H0 is rejected, which means the average value of science process skills and collaboration skills> 72, the results of paired sample t-test the value of pretest-posttest cognitive ability has the same Sig. (2-tailed) value and below 0.05 is 0,000 so H1 is accepted, meaning that there are differences in the average pretest-posttest results using LKPD based on collaborative teamwork learning so that there is an influence of student worksheets based on collaborative teamwork learning on student learning achievement as indicated by the average value of collaboration skills and science process skills> 72.